The Influence of Career Development and Perceived Organizational Support on Subjective Career Success: The Mediating Role of Career Commitment - Rahadi, Claudea; Syahrul, Laura; Lukito, Hendra (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Enhancing subjective career success is a crucial factor in achieving individual goals and success within organizations. This study aims to examine the influence of career development and perceived organizational support on subjective career success, with career commitment acting as a mediating variable. The population of this study comprises employees of the Standardization and Industrial Services Center (BSPJI) in Padang. A census sampling technique was employed, involving the entire population of 73 employees. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The findings indicate that perceived organizational support has a positive and significant effect on subjective career success. In contrast, career development, while exhibiting a positive relationship, does not have a statistically significant effect. Furthermore, career commitment is proven to mediate the relationship between perceived organizational support and subjective career success. However, it does not mediate the relationship between career development and subjective career success.